State of the world 2013 is sustainability still possible? - Assadourian, Erik; Prugh, Thomas; Starke, Linda; Worldwatch Institute (Washington, DC Island Press, 2013)
"In 'State of the World 2013: Is Sustainability Still Possible?', experts define clear sustainability metrics and examine various policies and perspectives, including geoengineering, corporate transformation, and changes in agricultural policy, that could put us on the path to prosperity without diminishing the well-being of future generations. If these approaches fall short, the final chapters explore ways to prepare for drastic environmental change and resource depletion, such as strengthening democracy and societal resilience, protecting cultural heritage, and dealing with increased conflict and migration flows."--Provided by publisher.
State of the world : a year in review / Alison Singer ; Beyond sustainababble / Robert Engelman -- The sustainability metric. Respecting planetary boundaries and reconnecting to the biosphere / Carl Folke ; Defining a safe and just space for humanity / Kate Raworth ; Getting to one-planet living / Jennie Moore and William E. Rees ; Sustaining freshwater and its dependents / Sandra Postel ; Sustainable fisheries and seas : preventing ecological collapse / Antonia Sohns and Larry Crowder ; Energy as master resource / Eric Zencey ; Renewable energy's natural resource impacts / Shakuntala Makhijani and Alexander Ochs ; Conserving nonrenewable resources / Gary Gardner -- Getting to true sustainability. Re-engineering cultures to create a sustainable civilization / Erik Assadourian ; Building a sustainable and desirable economy-in-society-in-nature / Robert Costanza ... et al. ; Transforming the corporation into a driver of sustainability / Pavan Sukhdev ; Corporate reporting and externalities / Jeff Hohensee ; Keep them in the ground : ending the fossil fuel era / Thomas Princen, Jack P. Manno, and Pamela Martin ; Beyond fossil fuels : assessing energy alternatives / T.W. Murphy, Jr. ; Energy efficiency in the built environment / Phillip Saieg ; Agriculture : growing food and solutions / Danielle Nierenberg ; Protecting the sanctity of native foods / Melissa K. Nelson ; Valuing indigenous peoples / Rebecca Adamson, Danielle Nierenberg,and Olivia Arnow ; Crafting a new narrative to support sustainability / Dwight E. Collins ... et al. ; Moving toward a global moral consensus on environmental action / Kathleen Dean Moore and Michael P. Nelson ; Pathways to sustainability: building political strategies / Melissa Leach ; Moving from individual change to societal change / Annie Leonard -- Open in case of emergency. Teaching for turbulence / Michael Maniates ; Effective crisis governance / Brian Martin ; Governance in the long emergency / David W. Orr ; Building an enduring environmental movement / Erik Assadourian ; Resistance : Do the ends justify the means? / Bron Taylor ; The promises and perils of geoengineering / Simon Nicholson ; Cuba : lessons from a forced decline / Pat Murphy and Faith Morgan ; Climate change and displacements / Michael Renner ; Cultivating resilience in a dangerous world / Laurie Mazur ; Shaping community responses to catastrophe / Paula Green ; Is it too late? / Kim Stanley Robinson
Includes bibliographical references (pages [381]-431) and index.
Keywords: Sustainable development